A vicarious, one-pot synthesis of benzo- and naphthofurans: Applications to the syntheses of stereumene B and paeoveitols. Issue 16 (18th April 2019) - Rashid, Showkat; Bhat, Bilal A.; Mehta, Goverdhan
Graphical abstract: Highlights: A deviation to Tanabe γ-lactone annulation is reported. This method provides one-pot access to benzofurans and naphtho[2, 3– b ]furans. Concise synthesis of stereumene B, paeoveitol D and (±)-paeoveitol are accomplished. Abstract: An interesting albeit unexpected deviation during attempted Tanabe γ-lactone annulation on 4-hydroxycyclohexanones has led to a general, one-pot synthesis of benzofurans and naphtho[2, 3– b ]furans from readily assembled precursors. The utility of this adaptable methodology has been demonstrated through concise syntheses of natural products, stereumene B, paeoveitol D and (±)-paeoveitol.